1977
DOI: 10.1159/000207861
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Blood Transfusion on the Immune Response of Children with Thalassaemia

Abstract: The effect of blood transfusions on the immune response of 46 thalassaemic children was studied. Cell-mediated immune response was evaluated by performing skin tests to specific (streptokinase-streptodornase and candidin) and nonspecific (dinitrochlorobenzene and phytohaemagglutinin) antigens. Antibody response to a specific antigen (tetanus toxoid) was estimated by measuring the tetanus antitoxin titre before and after vaccination. No gross impairment of cell-mediated immunity was elicited. The larger proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The selective depletion of T-lymphocytes in P-thalassaemia seems to be unassociated with impairment of cell-mediated immunity (Kanakoudi-Tsakalidis et al, 1977). It could be due to a depletion of particular T-cells, perhaps suppressor T-cells.…”
Section: Discussionmentioning
confidence: 94%
“…The selective depletion of T-lymphocytes in P-thalassaemia seems to be unassociated with impairment of cell-mediated immunity (Kanakoudi-Tsakalidis et al, 1977). It could be due to a depletion of particular T-cells, perhaps suppressor T-cells.…”
Section: Discussionmentioning
confidence: 94%
“…On the basis of these re ports we studied, in correlation to serum iron and ferritin levels, the quantitative peripheral T-subset distribution, as as sessed by means of a series of OKT mon oclonal antibodies (T3, T4, T6, Ts), in 14 patients with TI, 7 of them previously splenectomized. Intermediate thalassaemics were chosen for this investigation be cause they, unlike major thalassaemics, do not require blood transfusion, which could induce per se lymphocyte subset changes by an aspecific immunological stimulation [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study we assessed NK ac tivity and T lymphocyte subpopulations in homozygous beta thalassemia, a severe transfusion-dependent anemia, in which some studies of cell-mediated immunity have been so far reported [4,13,19,21]. Patients with hemoglobinopathies suffer rather frequently from bacterial and viral infections; furthermore, the incidence of malignancies in thalassemia major (TM) may be an issue of interest, since hyper transfusion regimens together with inten sive removal of iron excess have signifi cantly improved the outcome of the dis ease, and at present the life expectancy of these subjects is lengthened [ 16],…”
Section: Introductionmentioning
confidence: 99%